Successful Management of Acute Ischemic Stroke with Intravenous Thrombolysis and Implementation of Prehospital Stroke - Ni Made Ayu Candrayuni; Deddy Andaka (Neurointervention Working Group of Indonesian Neurological Association, 2025)
Highlight: Timely thrombolysis led to major neurological improvement in stroke patient. Early recognition and prehospital care enabled rapid stroke intervention. Case shows value of prehospital stroke systems for thrombolysis success ABSTRACT Introduction: Acute ischemic stroke (AIS) is a leading cause of disability and death worldwide. Timely administration of intravenous thrombolysis (IVT) significantly improves patient outcomes when delivered within the therapeutic window. Prehospital stroke care encompass the period from symptom onset to hospital arrival and includes both patient-to-hospital and inter-hospital transfers. Delays in prehospital stroke care represent a significant barrier to effective treatment. Case: A 68-year-old male presented with sudden left-sided weakness and slurred speech. A CT scan performed one hour after symptom onset showed no acute abnormalities (ASPECTS 10). He was transferred to the hospital 3.5 hours post-onset and received alteplase (67.5 mg). His door-to-needle time was 20 minutes, with an onset-to-needle time of 3 hours and 50 minutes. The patient showed significant improvement, with his NIHSS score decreasing from 11 to 2 within 30 minutes. Conclusion: Integrating IVT with robust prehospital stroke services enhances treatment efficiency and improves functional outcomes, setting a benchmark for optimal stroke management.